Tunable linear donor–π–acceptor conjugated polymers with a vinylene linkage for visible-light driven hydrogen evolution. Issue 12 (9th June 2021) - Han, Shitong; Huang, Tao; Pan, Yi; Zhao, Jiwu; Lin, Huan; Lin, Huaxiang; Ding, Zhengxin; Xi, Hailing; Long, Jinlin
Abstract : Extending the in-plane conjugation or/and increasing the electron push–pull interaction of linear D–π–A polymers with a vinylene linkage could broaden the visible-light absorption band, promote the charge separation and transfer and the photocatalytic hydrogen production. Abstract : This work demonstrated the rational design and synthesis of donor–π–acceptor (D–π–A) linear vinylene-linked polymers for visible-light driven H2 production with high efficiency. Extending the in-plane conjugation, enhancing the electron push–pull interaction or/and lowering the steric hindrance of the D–π–A type linear conjugated polymer could broaden the visible-light absorption band, promote the photogenerated charge separation and transfer, and thus improve the photocatalytic performance.